DEVELOPING CRITICAL THINKING SKILLS THROUGH LITERATURE IN THE ENGLISH CLASSROOM - G.Xolmurodova,; S.Muzaffarova, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores how literature can be utilized to foster critical thinking skills in the English classroom. The topic is important because English lessons today are expected to build more than grammar and vocabulary. Learners are also expected to analyze ideas, compare viewpoints, justify opinions, and draw clear conclusions. The article focuses on the teaching value of literary texts, especially short stories and other classroom-friendly texts, as tools for reflection, discussion, and deeper reading. The article  examines  how  literature-based  tasks  can  facilitate  interpretation,  evaluation, classroom  discussions,  and  independent  thinking.  A  qualitative  and  descriptive approach is used. Existing books and research articles are reviewed, and several short extracts from literary works are discussed through a simple structure: extract, simple analysis,  and  discussion.  Comparative  reading,  source  analysis,  and  method-based interpretation are also used in the study. The reviewed studies show that literature can improve reading, discussion, and critical response when tasks are designed clearly and when students are guided with purposeful questions. Recent studies also show that literature-based teaching can strengthen reading skills, classroom participation, and critical  thinking  in  EFL  contexts.  The  article  argues  that  literature  can  become  an effective and practical tool for the English classroom when text selection, task design, and teacher support are carefully planned.